Struktur Aset, Ukuran Perusahaan, Likuiditas, Profitabilitas, dan Nilai Perusahaan - Grediani, Evi; Dianingsih, Mita (E-Jurnal Akuntansi; Vol 32 No 4 (2022)DO - 10.24843/EJA.2022.v32.i04.p04, 2022)
This study aims to examine the factors that affect firm value. The data used in this study are trading companies listed on the Indonesia Stock Exchange between 2016-2020. The data sampling technique was purposive sampling. The data was obtained from the web of trading companies and the website of the Indonesian stock exchange. Testing the research hypotheses using regression analysis using SPSS 26. The results show that firm size and profitability affect firm value. While the variable structure of assets and liquidity have no effect on firm value. Research contributes to investors in assessing companies related to the transparency of the company's financial reporting. Keywords: Structure; Firm Size; Liquidity; Proitability; Firm Value